Parâmetros genéticos de caracteres quantitativos relacionados à produtividade de rebanhos selecionados da raça nelore - Guimarães, Nayanny Corrêa (2016)
Most of the Brazilian beef is produced in the Cerrado region, where beef cattle consists of zebu breeds well adapted to the creation of conditions in the tropics. Today, the biggest challenge for the beef cattle in the Cerrado is to optimize the economic potential in a sustainable manner, while preserving this biome rich in biological diversity. Despite this favorable scenario, economic agents involved in beef production and marketing process recognize the low levels of productivity of beef cattle in Brazil. In this way, to improve the Nellore productivity levels is essential for the country to avidly compete in the international market. Thus, the aim of this study was to estimate the components of (co) variances and genetic parameters of traits of economic importance, being, birth weight (BW), weight at 120 (P120) 210 (P210) 365 (P365) and 450 days of age (P450), adult cow weight (PAV), ribeye area (REA), fat thickness obtained between the 12th and 13th ribs (EG), subcutaneous fat thickness on the back (EGP8), scrotal circumference at 365 days of age (PE365), scrotal circumference at 450 days of age (PE450), age at first calving in months (IPP), and accumulated productivity in kilograms of calves weaned per cow / year (PAC) of Nelore cattle raised extensively on pasture. The data set for analysis in this study was obtained through five participating herds of Nelore Brazil Program of the National Association of Breeders and Researchers (ANCP), totaling 34,137 animals. Genetic parameters were estimated in univariate and two-trait animal models using the EM-REML algorithm available in the computational package REMLF90. Heritability estimates for direct additive effects were 0.27, 0.20, 0.20, 0.25, 0.36, 0.17, 0.37, 0.46, 0.10, 0.14, 0.53, 0.19, 0.25 for PN, P120, P210, P365, P450, PAV, PE365, PE450, IPP, PAC, AOL, EG and EGP8 respectively. The heritability for maternal additive effects were 0.04, 0.09, 0.09 and 0.04 for PN, P120, P210 and P365, respectively. The correlation between growth estimates of characters with the housing ranged from -0.72 to 0.97, and between growth and reproductive characters ranged from -0.70 to 0.97 and carcass characters with reproductive varied of -0.70 to 0.95, with all beneficial correlations. Estimates of heritability for the traits studied, except the IPP and PAC obtained in this study allow us to conclude that there is genetic variability in the studied herds, indicating the possibility of genetic progress if they are included as selection criteria. The obtained genetic correlations were positive, selection for increased a result in the improvement of the other.